2003
DOI: 10.1161/01.cir.0000070948.37545.e0
|View full text |Cite
|
Sign up to set email alerts
|

Noncultured, Autologous, Skeletal Muscle Cells Can Successfully Engraft Into Ovine Myocardium

Abstract: Background-There is compelling evidence showing that cellular cardiomyoplasty can improve cardiac function.Considering the potential benefit of using noncultured muscle cells (little time, lower cost, reduced risk of contamination), we investigated the feasibility of grafting cells obtained directly after enzymatic dissociation of skeletal muscle biopsies into ovine myocardium. We hypothesized that those noncultured muscle cells would engraft massively. Methods and Results-Autologous, intramyocardial skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Immunohistochemical studies used a standard three‐step avidin‐biotin‐immunoperoxidase method [24]. An antibody against the proliferation marker Ki‐67 was obtained from Dako (Trappes, France).…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical studies used a standard three‐step avidin‐biotin‐immunoperoxidase method [24]. An antibody against the proliferation marker Ki‐67 was obtained from Dako (Trappes, France).…”
Section: Methodsmentioning
confidence: 99%
“…Focal adhesion‐associated proteins participate in cellular events that confer myofibroblast contractility and migration. Myofibroblasts may be characterized by increased expression of embryonic smooth muscle myosin heavy chain (SMemb) (Frangogiannis et al,2000) and extra domain‐A (ED‐A) fibronectin (Borenstein et al,2003); the latter protein is bound to fibronexus adhesion complexes in vivo and supermature focal adhesions in vitro (Tomasek et al,2005). Thus, ED‐A fibronectin is critical for linking the extracellular matrix to intracellular cytoskeleton, and for exerting mechanical traction on the matrix by means of cellular contraction.…”
Section: Introductionmentioning
confidence: 99%
“…4 Reinecke and Murry have demonstrated the risk of tissue overgrowth distorting the LV contour when a large number of myoblasts were transplanted as a single bolus. 9 In our study, none of the LV undergoing 3 episodes of myoblast implantation demonstrated either distortion or distension. In future experiments, the most appropriate number of cells and episodes of skeletal myoblast transplantation should be determined.…”
Section: Discussionmentioning
confidence: 43%
“…Within the past several years, cellular therapy (cardiomyoplasty) has emerged as a novel concept for endstage heart failure after MI. 1 Experimental studies have used different cell types, such as cardiomyocytes, 2,3 skeletal myoblasts, [4][5][6][7][8][9][10][11][12][13][14][15] fibroblasts, 8 embryonic stem cells 16 and bone marrow stem cells. 14,[17][18][19] Of these, skeletal myoblast transplantation appears to be more relevant from a clinical point of view because skeletal myoblasts can be obtained by routine muscle biopsy from heart failure patients, and then transplanted autologously without the risk of graft rejection.…”
mentioning
confidence: 99%